DETERMINATION OF EMPLOYEE RELATION PRACTICES OF MANAGERS OF SMALL AND MEDIUM ENTERPRISES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study determined the employee relation practices of managers of small and medium enterprises in Anambra State. One research question guided the study and two null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted using a population of 2, 610 managers of SMEs in Anambra State. A sample size of 347 was selected. A structured questionnaire developed by the researcher was used for data collection. The instrument was validated by three experts in Business Education Department. Cronbach alpha was used to establish the reliability of the instrument. The reliability index obtained was r = 0.76. Data were analyzed using mean, standard deviation, t-test and ANOVA. Mean was used to answer the research question and standard deviation used to explain how the responses of the respondents varied. t-test and ANOVA were used to test the hypotheses at 0.05 level of significant. The results showed that managers agreed on the employee relation practices adopted in their small and medium scale enterprises in Anambra State. The results also showedthat there was no significant difference in the mean responses of managers on the employee relation practices adopted in their small and medium scale enterprises in Anambra State based on size of enterprise and years of experience. Based on the findings, the researchers recommended among others, that the management of SMEs should value the contribution andideas shared by employees and empower employees to maximize their individual talents in order to make effective decisions.
Keywords: Employee relation, managers and small and medium enterprises.